As contribuições da vida e obra de Urbano Zilles para o estudo das relações entre ciência e religião na educação cientifica - Peixoto, Cintia Terezinha Barbosa (2022)
The possible relationships between scientific knowledge and religiosity of students and teachers play an important role in certain science lasses, since some scientific knowledge goes against the beliefs and convictions of these students, coming from their social environments, which can cause cognitive conflicts. and resistance to science learning. Therefore, the teacher is challenged to be able to discuss deeply the relationship between Science and Religion for the promotion of an intercultural, careful, respectful Scientific Education and, at the same time, capable of making the scientific understanding of the world more complete. For this, the teacher needs a vision of Science and Religion in which this discussion makes sense. In this scenario, the search for theoretical/philosophical contributions was made from the study of the life and works of Urbano Zilles, analyzing the arguments of the philosopher and theologian about Religion, Science, faith and atheism, in addition to the relationship between these fields, with the objective of broadening the understanding of the concepts and epistemological conceptions involved in the implications in school education and listing subsidies so that the Relations between Science and Religion are better understood and fruitful in Scientific Education. The contextualization of the presented problem was made from an investigation of the theme of the relations between Science and Religion in national and international research, identifying relevant aspects addressed in these researches, such as the diversity of perspectives of students and teachers about the relationship between the scientific and religious fields; pointing out that this topic should be part of the education of Science teachers; the indication of an intercultural education as a way of approaching scientific knowledge respecting the points of view arising from Religion or from the student's culture and the identification that the relationship between creationism and evolutionism presents itself as a challenge to the science teacher. Considering that the research topic has a historical background that is decisive for understanding the complexity of the relationship between Science and Religion, a historical overview of how these relationships developed is presented. In addition, practical implications, possibilities for advancement and possible obstacles that actions with the same purpose will face are pointed out.